Improving Students’ Interest in Learning English by Using Games - Mery Silalahi (International Journal of Theory and Application in Elementary and Secondary School Education, 2019)
One of the teachers' efforts to improve students' interest in English is learning English through games. The learning process by playing games can provide more interactive English learning atmosphere so that it is expected to improve the ability of students in vocabulary development. Learning through games can provide several benefits. First, what is learned by students is not only in the form of mere knowledge of reason but experienced in real terms; such experiences are difficult to forget. Second, the lessons provided are pleasantly accepted, because they are related to the nature of the game which is entertaining and joyful. Thus, the possibility of student rejection of what is taught can be minimized. Third, because the game is fun, playing at the same time generates great interest for students about certain things or topics. Based on the reasons, it is expected that through these fun activities that is games; students' interest in learning English can be improved.